Evaluation of Centering Ability in Artificially Curved Canals with Three Thermomechanically Treated NiTi Instruments: Blue, Pink and Gold - Félix, Alejandro; Aranguren, José; Navarrete, Natalia; Perez, Alejandro R. (Iranian Endodontic Journal, 2025)
Introduction: The present study aimed to evaluate the instrumentation time and transportation ability of three file sequences sharing the same physical properties (diameter, tip design, cross-sectional shape, and taper), each manufactured entirely of one single alloy type (Pink, Blue, or Gold). Materials and Methods: One hundred and eighty simulated curved resin canals were instrumented using the BlueShaper system, with full Z1-Z4 sequences, each made entirely of a single alloy type (Pink, Blue, or Gold). Images before and after instrumentation of each specimen were overlaid with Photoshop software to evaluate centering ability in the coronal, middle, and apical thirds. Data were analyzed using one-way analysis of variance (ANOVA) with post hoc multiple comparisons or the non-parametric Kruskal-Wallis test for intergroup analysis. Results: No significant differences were found between the different alloys in the centering ability of the simulated canals in the coronal third (P>0.05). The Blue alloy of the BlueShaper system showed significantly less transport ability in the middle third than Pink and Gold alloys (P<0.05). A significantly lower centering ability (P<0.001) was observed in the apical third between the Blue and Pink alloys than the Gold alloy. Conclusions: It was concluded that the Blue alloy performed better than the Pink and Gold alloys in the middle and apical thirds. The pink alloy performed better than the Gold alloy in the apical third.